An Advanced High Performance Maximum Power Point Tracking Method with Ant Colony and Particle Swarm Optimization Method Using Interleaved Boost Converter - Nivetha V; G. Vijaya Gowri; Elamathy A (Institute of Advanced Engineering and Science, 2015)
To obtain efficient maximum power point tracking operation under varying and steady state environmental conditions which is based on Ant Colony Optimization (ACO) combined with Particle Swarm Optimization (PSO) that controls an interleaved DC-DC converter connected at the output of PV array and maintains a constant input-power load. The operation of maximum power point tracking is to adjust the power interfaces so that the operating characteristics of the load and the photovoltaic array match at the maximum power points. The simulation is based on the computed algorithms which show very good perspectives. The searching routine is done in less than 15 steps and takes less than 50ms. The tracking accuracy is better than those found in conventional methods. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7900